PENGARUH KELENGKAPAN PERSYARATAN KLAIM PASIEN BPJS UNIT RAWAT INAP TERHADAP KETERLAMBATAN KLAIM RSUD MAJALAYA - Rukmini Minii; Irda Sari (INFOKES (Informasi Kesehatan), 2022)
This study claims to know the effect of the completeness of the BPJS Patient Claim Requirements In the Inpatient Unit on the Delay In Claims at The Majalaya Regional General Hospital. The research method used by the author is quantitative with a descriptive approach. Data collection techniques used are observation, interviews, literature studies and questionnaires. The sampling technique used was the purposive sampling technique with a sample of 97 claim files for BPJS patients in inpatient units from January to March. Based on a statistical test with a significance a = 10% (0,1) or a confidence level of 90%, it shows the effect of incomplete claim requirements for BPJS patients in inpatient units on the delays in claims at Rumah Sakit Umum Daerah Majalaya that the average claim that can be claimed is 70% and those experiencing 30% delay. The problems found from the research carried out were (1) Inaccuracy of coding and actions that have been given to the patient, (2) Incompatibility of filling or inputting patient data, (3) There is no SOP regarding inpatient BPJS claims, (4) There are some scan files that are not clear, (5) Often experience internet network disturbances.Keywords: INA-CBGs Claim, Hospitalization, Delay